RELEVANSI PENDIDIKAN DENGAN SURAH AL-‘ASHR - Desriadi, Desriadi; Hardiman, Dodon; Faraditsi, Fauzia (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2023)
This research is motivated by the fact that the education process so far has not been fully successful in developing Indonesian people with character. In fact, some say that education has failed, because many school graduates or graduates are skilled at answering exam questions, have intelligent brains, but are mentally and morally weak. Education has an important role in instilling faith, patience, independence, discipline, responsibility, creativity and noble character. Surah Al-'Ashr contains several pillars of education which can be used as guidelines by students and educators in carrying out the daily learning process. This research is library research (library research), namely research carried out in libraries or museums on existing materials in the form of books, magazines or other documents. The primary data source for this research is the Al-Qur'an Surah Al-